P Wave Dispersion in Patients with Generalised Anxiety Disorder - Tabara, Muhammed Fatih; Cakar, Mustafa; Baykara, Sema; Gurok, Mehmet Gurkan; Korkmaz, Sevda; Mermi, Osman; Atmaca, Murad (Yuzuncu Yil Universitesi Tip Fakultesi, 2026)
Introduction: Generalised anxiety disorder (GAD) is a prevalent condition defined by persistent, irrational, and uncontrollable worries regarding various daily activities. While previous research has identified alterations in atrial electrophysiology in conditi ons such as panic disorder and obsessive-compulsive disorder, P-wave dispersion (Pd) remains largely unexplored in GAD. This study aimed to evaluate Pd parameters—specifically maximum P-wave duration (Pmax) and minimum P-wave duration (Pmin)—in patients with GAD to identify potential cardiac risks associated with chronic anxiety. Materials and Methods: A case-control study was conducted involving 20 patients diagnosed with GAD via the SCID-5-CV and 20 age-and sex-matched healthy controls. Standard 12-lead surface electrocardiograms (ECGs) were recorded at a paper speed of 50 mm/s. Pmax and Pmin were manually measured by a blinded cardiologist using high-precision callipers, with Pd calculated as the difference between the two values (Pmax-Pmin). Symptom severity was assessed using the Hamilton Anxiety Rating Scale (HARS). Results: Statistical analysis revealed that Pmax and Pmin values were significantly elevated in patients with GAD compared to healthy controls. Notably, the primary outcome measure—mean P-wave dispersion—was significantly higher in the patient cohort (50.74 ± 6.10 ms) than in the control group (35.32 ± 3.79). Conclusion: Patients with GAD demonstrate a distinct electrophysiological profile characterised by a global prolongation of atrial conduction parameters and significantly increased P-wave dispersion. These findings suggest that the "mental" worry of GAD carries a measurable "physical" cardiac risk, necessitating closer clinical monitoring of atrial electrophysiology, particularly when p rescribing psychotropic medications that may influence cardiac conduction. © 2026, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: Anxiety disorders; atrial function; case-control study; electrocardiography